Digital Policy Integration for Poverty Reduction: Leveraging e-Government and Data Interoperability - Riska Sarofah; Hilal Ramdhani; Sidik Firmadi (Universitas Teuku Umar, 2026)
This study aims to analyze the integration of digital policies through e-government and data interoperability in supporting effective poverty alleviation in Tasikmalaya City. The approach used is a qualitative case study design, through in-depth interviews with relevant agencies such as Bappelitbangda, the Social Service, the Health Service, the Education Service, the Communication and Information Service, the Manpower Service, and users of digital services. The results show that data interoperability enables faster, more accurate, and more efficient cross-sectoral information exchange, and supports decile-based poverty classification, which serves as the basis for developing more targeted job training and social assistance programs. However, challenges such as differences in information systems between agencies, limited technological infrastructure, lack of human resource capacity, and cross-institutional coordination remain obstacles to optimizing digital policy implementation. This study also underscores the importance of multi-stakeholder collaboration between the government, the private sector, and educational institutions in improving the quality of human resources and creating innovative public services. These findings align with the e-Government Interoperability Framework (eGIF) and provide theoretical and practical contributions to the development of adaptive and sustainable digital governance at the local level. This research recommends strengthening regulations, increasing digital capacity, and developing an integrated monitoring and evaluation system to support the successful integration of e-government within the context of data-driven social policy.